Robust study design is as important on the social as it is on the ecological side of applied ecological research - St,John FAV; Keane,AM; Jones,JPG; Milner-Gulland,EJ (Journal of Applied Ecology, 2014)
1. The effective management of natural systems often requires resource users to change their behaviour. This has led to many applied ecologists using research tools developed by social scientists. This comes with challenges as ecologists often lack relevant disciplinary training.2. Using an example from the current issue of Journal of Applied Ecology that investigated how conservation interventions influenced conservation outcomes, we discuss the challenges of conducting interdisciplinary science. We illustrate our points using examples from research investigating the role of law enforcement and outreach activities in limiting illegal poaching and the application of the theory of planned behaviour to conservation.3. Synthesis and applications. Interdisciplinary research requires equal rigour to be applied to ecological and social aspects. Researchers with a natural science background need to access expertise and training in the principles of social science research design and methodology, in order to permit a more balanced interdisciplinary understanding of social–ecological systems.